Good Muslims and Good Citizens: How Fiqh al-Aqalliyyat Solves the Problems of Muslim Minorities in the West - Adel Ibrahim A. Alturki; Jamal; Ahmad Wasito (Peradaban Journal of Religion and Society, 2023)
Fiqh al-aqalliyat articulates the importance of providing a normative basis for religious, social, and political activities for Muslim minorities in non-Muslim societies. It aims to help those who seek a healthy middle way between being a good Muslim on the one hand and being a good citizen on the other. The view of Fiqh al-aqalliyat does not only provide a way out for the Muslim minority to carry out religious obligations in unique and special situations. More than that, Fiqh al-aqalliyat also provides a conceptual basis for Muslim minorities to integrate and become part of Western society.